Konsentrasi dan Karakter Siswa Madrasah Ibtidaiyah: Tinjauan atas Partisipasi Orang Tua, Interaksi Guru, dan Program Literasi - Didit Darmawan; Nur Hawadatul Khosla (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyse the role of parental involvement, teacher interaction, and literacy programmes in shaping pupils’ concentration, character, and academic achievement at Islamic primary schools (Madrasah Ibtidaiyah). The study employed a literature review using a qualitative approach, conducted through a systematic search and review of relevant journal articles, books, and research reports. Data were analysed using thematic synthesis to identify patterns, key findings, and the interrelationships between the variables under study. The results indicate that parental involvement contributes to building students’ self-regulation and character from within the family environment; positive teacher interactions play a role in strengthening concentration and learning attitudes at school; and literacy programmes that are consistently designed and implemented support the development of students’ concentration, character, and academic achievement. These three factors complement one another in forming a primary education ecosystem that supports students’ holistic development.